Investigation on thermal analysis of conical coil heat exchanger. (November 2015) - Purandare, Pramod S.; Lele, Mandar M.; Gupta, Raj Kumar
Highlights: Conical coils with various cone angle and tube diameters are considered for analysis. Nu increases with tube side flow rate and reduces with shell side flow rate. Nu reduces from helical to conical to spiral coil and increase in tube diameter. Friction factor ( f ) is a function of flow rate, tube diameter curvature ratio and cone angle. Abstract: The experimental investigation on thermal analysis of conical coil heat exchanger is presented in this paper. Fifteen conical coils of different cone angles (0° (helical), 45°, 90°, 135°, 180° (spiral)), with three different tube sizes (ID × OD, 8 × 10, 10 × 12 and 12 × 15) are fabricated and analysed with, same average coil diameter ( Dm  = 200 mm) and tube length ( L  = 3 m). The experimentation is carried out with hot and cold water of flow rate 10–100 lph ( Re – 500 to 5000) and 30–90 lph respectively. The observations recorded were leads to analysis the heat exchanger for heat transfer and pressure drop characteristics at different flow rate of cold and hot fluid. The various parameters (heat transfer coefficient ( hi ), Nusselt number ( Nu ) effectiveness ( ε ) and friction factor ( f )) are estimated for the heat exchanger. The analysis indicates that, Nu and f are the functions of flow rates, tube diameter, curvature ratio and cone angle. Nu increase with increase in tube side flow rate whereas it reduces with increase in shell side flow rate, increase in cone angle and increase in tube diameter. The effects of cone angle, tube diameter and fluid flow rates on heat transfer and pressure drop characteristics are detailed in this paper. The empirical correlations are proposed to bring out the physics of the thermal aspects of the conical coil heat exchangers.